Implementation of a comprehensive competency‐based transoral robotic surgery training curriculum with ex vivo dissection models. Issue 10 (6th May 2016) - Sobel, Ryan H.; Blanco, Ray; Ha, Patrick K.; Califano, Joseph A.; Kumar, Rajesh; Richmon, Jeremy D.
ABSTRACT: Background: Despite its increasingly widespread adoption of transoral robotic surgery (TORS), there is still no uniform training curriculum. The purpose of this study was to describe the results of our novel TORS curriculum training program in which we introduce ex vivo dissection models for radical tonsillectomy and base of tongue (BOT) resections. Methods: Prospective blinded data collection and objective assessment of a novel training curriculum. Trainee performance was evaluated on objective structured assessments of technical skills (OSATS) metrics, measured resection time, and margin analysis. Additionally, 4 expert TORS surgeons completed the ex vivo dissections. Results: Trainees achieved OSATS scores similar to those of experts in both the BOT resection and radical tonsillectomy models. Peripheral and deep surgical margin measurements in the BOT model were significantly improved after training and were comparable to experts. Conclusion: This graduated curriculum provides a realistic training experience to develop competency with oropharyngeal resections before transition to the operating room. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–1563, 2016